Nepal’s Trade Sector: Review, Repercussions and Recommendations - Pant, Bhubanesh (NRB Economic Review, 2005)
That the trade sector plays a highly instrumental role in attaining high and sustainable economic growth is indisputable. However, Nepal’s policy regime has not been very effective in improving trade competitiveness. Although policy measures have been announced both to identify new exportable products and encourage diversification of export markets, these have hardly been executed. Weak infrastructure, poor human resources, absence of quality standardization of exports, dearth of a strong legal framework and frequent policy reversals, among others, have restricted the country in improving its international competitiveness. Still, owing to the emerging trend of a competitive and market-oriented global economy, these issues need to be properly addressed. With reference to regional and multilateral agreement, the country should undertake a two-pronged strategy according priority to multilateral trade negotiations under the World Trade Organization as well as to strive for effective and meaningful regional trading arrangements such as the South Asian Free Trade Area (SAFTA) and the Bay of Bengal Initiative for Multi-sectoral Technical and Economic Cooperation Free Trade Area (BIMST-EC FTA) which it is currently pursuing. Other measures suggested by this paper for boosting trade competitiveness include, among others, technological upgrading, investment in infrastructure, appropriate legal framework compatible with regional and multilateral agreements, new trade policy, setting up of export processing zones and credible policy.